Taxane-based Induction Chemotherapy Plus Concurrent Chemoradiotherapy in Nasopharyngeal Carcinoma: Prospective Results from a Non-endemic Cohort. Issue 12 (December 2019) - Ghosh-Laskar, S.; Pilar, A.; Prabhash, K.; Joshi, A.; Agarwal, J.P.; Gupta, T.; Budrukkar, A.; Murthy, V.; Swain, M.; Noronha, V.; Patil, V.M.; Pai, P.; et al.
Abstract: Aims: To report the outcomes of induction chemotherapy (ICT) followed by chemoradiotherapy (CTRT) for a large cohort of locoregionally advanced nasopharyngeal cancer (LA-NPC) from a non-endemic region. Materials and methods: Between January 2008 and July 2015, 201 patients with histologically proven, non-metastatic NPC were treated with ICT followed by CTRT at our institute. All the patients received two to three cycles of a taxane-based ICT regimen. Radiotherapy was delivered using an intensity-modulated radiotherapy (IMRT) technique in all patients. Results: After a median follow-up of 37 months (range: 7–110 months), the 3-year disease-free survival (DFS), locoregional relapse-free survival (LRFS), distant metastasis-free survival (DMFS) and overall survival of the entire cohort was 72, 85, 83 and 87.4%, respectively. On multivariate analysis, histology was an independent predictor of DFS, LRFS and overall survival, with keratinising squamous cell carcinoma histologies predicting a worse outcome. The nodal stage was an independent predictor of DFS, DMFS and overall survival. Age, gender, ethnicity, tumour stage and response to ICT did not significantly affect any of the outcomes. Grade 2 or worse subcutaneous fibrosis was seen in 19% of patients at last follow-up and grade 2 or worse xerostomia was seen in 24% of patients. Thirty-nine per cent of patients developed clinical hypothyroidism at last follow-up. Conclusion: ICT followed by concurrent CTRT in the IMRT era provides excellent locoregional control, distant control and overall survival rates in patients with LA-NPC. However, distant failure continues to be a problem and may require further systemic intensification. Highlights: Reports outcomes with the addition of induction chemotherapy in nasopharyngeal cancer. Induction chemotherapy and chemoradiotherapy provides good locoregional and distant control. Distant failure continues to be a problem and requires further systemic intensification.